Inmotics: sustainability and comfort (2017)
The Olympic Games produce a long-lasting social, urban, cultural and economic impact in the host cities. For the specific case of the Youth Olympic Games, which will be held in the city of Buenos Aires, Argentina, a proposal has been selected to build an Olympic village that would function as social housing after hosting the games participants. Moreover, the International Olympic Committee requires and promotes the principle of environmental sustainability; consequently, host cities must adapt to host the event without losing sight of the optimal management of resources. In this context, technologies such as building automation become relevant and applicable to meet the objectives of providing quality of life and work without neglecting the efficient use of energy. Furthermore, this solution comes with great challenges that serve to promote the advancement of science and social commitment.